CURRENT PRINCIPLES AND TRENDS OF ATRIAL FIBRILLATION PHARMACOTHERAPY - Yu. A. Bunin (Столичная издательская компания, 2016)
Data on atrial fibrillation (AF) epidemiology and AF influence on the risk of cardiovascular complications are presented. Principles and tactics of AF therapy are discussed in accordance to evidence based medicine and European society of cardiology Guidelines. Algorithms for choice (on the basis of risk stratification) of different antiarrhythmic drugs and anticoagulants are described. Perspectives in improvement of efficacy and safety of AF therapy are reviewed.